2017
DOI: 10.1016/j.jsxm.2016.12.237
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Psychosocial Factors Related to Sexual Dysfunctions in Premenopausal Women∗

Abstract: Introduction The female sexual response is complex and influenced by several biological, psychological, and social factors. Testosterone is believed to modulate a woman's sexual response and desire, because low levels are considered a risk factor for impaired sexual function, but previous studies have been inconclusive. Aim To investigate how androgen levels and psychosocial factors are associated with female sexual dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Psychiatric disease is the most important risk factor for women's sexual dysfunction. [1][2][3][4] This remains true in the context of chronic diseases known to interrupt the neurovascular basis of sexual physiology. Thus, depression, rather than the burden of physical disease or severity of complications, is the independent factor determining presence or absence of sexual dysfunction in women living with diabetes, 5 multiple sclerosis, 6 renal failure 7 or rheumatic disease 8 as well as those with a history of past childhood sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric disease is the most important risk factor for women's sexual dysfunction. [1][2][3][4] This remains true in the context of chronic diseases known to interrupt the neurovascular basis of sexual physiology. Thus, depression, rather than the burden of physical disease or severity of complications, is the independent factor determining presence or absence of sexual dysfunction in women living with diabetes, 5 multiple sclerosis, 6 renal failure 7 or rheumatic disease 8 as well as those with a history of past childhood sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“…However, this cycle of responses must be understood within an intrapersonal and interpersonal context. As previously mentioned, factors as depression or the length of relationship have been associated with FSD [8, 9]. For many women, the contemporary phases of the sexual response cycle may vary in sequence, overlap, repeat, or even be absent, during all or some sexual encounters [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in libido and in sexual frequency were seen in postmenopausal women who received weekly intramuscular injections of testosterone [11]. Sexual desire was significantly associated with levels of free testosterone (FT) and androstenedione in premenopausal women, but FSD in general was not associated with androgen levels [9]. A population-based study of over 1400 randomly selected women aged 18 to 75 years showed no single androgen level to be predictive of low sexual function [12].…”
Section: Introductionmentioning
confidence: 99%
“…85 Early follicular phase levels of total and free testosterone, androstenedione, and dehydroepiandrosterone sulfate (DHEA-S) have been positively correlated with self-reported sexual desire in premenopausal women aged 25-44 years not using hormonal contraception, 83 whereas no correlation was found in women with HSDD. 86 A recent study of women aged 18-39 years, with regular menstrual cycles, not using any sex steroid therapy who had sex steroids measured by LC-MS/MS, found weak positive associations between both sexual desire and sexual pleasure and DHEA and androstenedione. 84 Orgasm was positively correlated with both testosterone and androstenedione.…”
Section: Do Androgen Levels Correlate With Sexual Function and Predict Hsdd?mentioning
confidence: 99%